The interaction of occupational stress, mental health, and cytokine levels on sleep in Xinjiang oil workers: A cross-sectional study - Li, Xue; Xue, Qiaoyun; Yi, Xiaoting; Liu, Jiwen (Frontiers in Psychiatry, 2022)
Background Sleep occupies one third of a person’s life, and good sleep quality is an important factor to ensure good health. Purpose This study investigated and analyzed the occupational stress, mental health and sleep quality of oil workers, analyzed the effects of occupational stress and mental health on sleep, and explored the effects of the interaction between occupational stress, mental health and cytokines on sleep. Materials and methods In this study, stratified cluster random sampling was used to conduct a cross-sectional survey on the occupational stress, mental health and sleep quality of 1,141 oil workers in the Occupational Health Examination Department of Karamay Central Hospital, from June 2019 to January 2020, and 30% of the participants were randomly selected for measurement of their cytokine levels: interleukin 2 (IL-2), interleukin 6 (IL-6), interleukin 8 (IL-8), and tumor necrosis factor α (TNF-α). The objectives were to analyze the effects of occupational stress and mental health on sleep quality, and to explore the effects of occupational stress, mental disorders and cytokine interactions on sleep. Results There were 646 individuals (56.6%) who suffered from sleep disorders; the incidence of sleep disorders differed according to sex, age, professional title, working years, type of work and shift (P < 0.05). The scores for occupational stress, mental health, and sleep quality were positively correlated (P < 0.05). Multivariate logistic regression analysis showed that age (30–45 years) (OR = 1.753, 95% CI: 1.067–2.881), junior college and above (OR = 1.473, 95% CI: 1.025–2.118), borehole operation (OR = 2.689, 95% CI: 1.508–4.792), extraction of oil (OR = 2.405, 95% CI: 1.229–4.705), drilling (OR = 1.791, 95% CI: 1.017–3.155), shift work (OR = 2.144, 95% CI: 1.615–2.846), occupational stress (OR = 1.007, 95% CI: 1.002–1.013), and mental disorders (OR = 1.020, 95% CI: 1.009–1.032) are risk factors for sleep disorders. In the high occupational stress group and the mental disorders group as the control group, the results showed that the interaction between IL-2 and moderate occupational stress (OR = 0.778, 95% CI: 0.778–0.942), IL-2 and non-mental disorders (OR = 0.398, 95% CI: 0.398–0.468) were protective factors for the occurrence of sleep disorders. The results of structural equation modeling analysis showed that occupational stress and mental health had positive predictive effects on IL-2 level and sleep quality [normalized path coefficients (β) were 0.10\0.06\0.05\0.71, respectively]. Occupational stress had a direct positive predictive effect on mental disorder (β = 0.25), and sleep disorder had a direct negative predictive effect on IL-2 concentration (β = −0.21). Conclusion Oil workers have serious sleep problems, so effective measures should be taken to reduce occupational stress and relieve mental health problems, and cytokine levels can be used as a predictor of sleep disorders.